Manajemen Diri Sebagai Fondasi Pembentukan Karakter: Kajian Konseptual, Mekanisme Internalisasi Nilai, dan Implementasi Langsung pada Siswa - Lyra Laililrizqi; Sri Minarti (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the concept of self-management as a basis for character formation from the perspective of psychology and education, explain the mechanism of self-management in the internalization of character values, and describe the implementation of self-management in building student character at SDN Dukuh Kidul, Ngasem, Bojonegoro. This study uses a descriptive qualitative approach by combining conceptual study and implementation in the context of elementary schools. Data collection techniques were carried out through observation, interviews, and documentation. The data were analyzed qualitatively through three stages, namely data condensation, data presentation, and drawing conclusions. The findings indicate that self-management serves as an essential foundation for character formation because it involves the ability to regulate thoughts, emotions, and behavior consciously. The mechanism of self-management operates through self-regulation, self-control, and self-evaluation, which transform moral values from normative knowledge into habits internalized by students. In its implementation at the elementary school level, self-management can be fostered through habituation, discipline reinforcement, teacher modeling, self-reflection, and the creation of a supportive learning environment. These findings affirm that effective character formation depends not merely on external supervision, but also on students’ ability to manage themselves independently, consistently, and responsibly.